Penguatan Etika Digital dalam Membangun Personal Branding Remaja di Media Sosial melalui Pendekatan Digital Public Relations - Anindita Anindita; Melly Ridaryanthi; Yuni Tresnawati; Teguh Setiawan (Yayasan Literasi Sains Indonesia, 2025)
This community service program aims to strengthen digital ethics awareness and build positive personal branding among teenagers through a Digital Public Relations approach. The program is driven by the increasing use of social media among teenagers, which has not yet been accompanied by adequate awareness of digital behavioral ethics and the importance of building a healthy self-image in the online sphere. The activities were conducted in person at SMKN 2 South Tangerang, involving more than 20 students as active participants. The program was designed as participatory training and interactive sessions covering topics on digital ethics, online reputation management, and strategies for building consistent, professional, and ethical personal branding. Participants were also given the opportunity to directly practice shaping their digital identity through social media platforms relevant to their character and goals. Evaluation results showed that the program successfully improved participants’ understanding and practical skills in responsible social media use. The satisfaction level was also high, with more than 90% expressing interest in joining similar activities in the future. This program also supports the achievement of Key Performance Indicators (KPIs) and the implementation of the “Merdeka Belajar Kampus Merdeka” (MBKM) initiative through the active involvement of lecturers and students in the community empowerment process.